5.71=-log(x)

Simple and best practice solution for 5.71=-log(x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5.71=-log(x) equation:


Simplifying
5.71 = -1log(x)

Multiply glo * x
5.71 = -1glox

Solving
5.71 = -1glox

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add 'glox' to each side of the equation.
5.71 + glox = -1glox + glox

Combine like terms: -1glox + glox = 0
5.71 + glox = 0

Add '-5.71' to each side of the equation.
5.71 + -5.71 + glox = 0 + -5.71

Combine like terms: 5.71 + -5.71 = 0.00
0.00 + glox = 0 + -5.71
glox = 0 + -5.71

Combine like terms: 0 + -5.71 = -5.71
glox = -5.71

Divide each side by 'lox'.
g = -5.71l-1o-1x-1

Simplifying
g = -5.71l-1o-1x-1

See similar equations:

| 2ln(4x)+5ln(7x)=6 | | (d+2)=6 | | B=1-18/4 | | X^2+10x-8=10 | | 3x-3x=3-1 | | -4x-5y=10 | | 2.3=[(0.785)(x2)(14)(7.48)]/[(0.785)(60)(60) | | 4+5lnx=2 | | 9z-z=-1+4z-3-4 | | 5XZ=30 | | 5f/5=35/5 | | 2x-4=87-11x | | 7y=-7*7-35 | | 3b^2-b-14=0 | | 20x+10=60 | | 2x+3.4=2x+3.4 | | 3(2x-4)-4x=16 | | 2(0)+(y)-6(0)=30 | | -2x+7=12x-6 | | -11+x=7x+5 | | 0=a^2+14a+36 | | 2y^2+7=5 | | 3=3x-6x^2 | | 17-(4-6z)+4=21 | | 2x^2+10-6=0 | | 3a=15+3 | | x/136=1.5 | | 7x-15=36 | | (2k+1)=5 | | r+n=12.5 | | 3n^2-4=26 | | (5t^2-t+2)+(-4t^2+3t+7)= |

Equations solver categories